The Impact of Noise Pollution on Workers Health in Selected Industries of Mirzapur Industrial Area, Tangail, Bangladesh - Alam, S; Akter, ST; Sheikh, MS; Bahar, I (Journal of Environmental Science and Natural Resources, 2017)
The unwanted and intolerable sound causes noise. The study was conducted through interviewing of workers and measuring of noise levels on six types of industries. The data were collected on April, May and June, 2013. The data of noise levels were measured at main gate, administration office and working place of the selected industries. The noise level at the working places during day time of the selected industries were 81.50 dB (textile mill), 104.20 dB (cotton mill), 90.50 dB (jute mill), 95.90 dB (spinning mill), 89.25 dB (knit and garments factory) and 83.50 dB (knitting factory), respectively. All the recorded noise level data in working places of the industries exceeded the DoE standard (75 dB at day time and 70 dB at night time) that caused noise pollution. The important contributors of noise pollution were machineries and overcrowding of the workers in the industry. Most of the common impacts of noise pollution were headache, heart diseases and hearing problem. To resolve the noise problem in industry it was suggested to eliminate the noise sources substituting noisy machineries and so on. J. Environ. Sci. & Natural Resources, 9(2): 155-160 2016